1988
DOI: 10.1159/000163461
|View full text |Cite
|
Sign up to set email alerts
|

Human Trophoblast Glycoproteins Defined by Monoclonal Antibody 1D2

Abstract: A cell surface antigen has been defined by a monoclonal antibody 1D2, raised following immunisation with lectin-purified syncytiotrophoblast glycoproteins. 1D2 was nonreactive with any one of 8 common trophoblast proteins in immunodot. Analysis of nonreduced western blots of syncytiotrophoblast microvillous plasma membrane (StMPM) protein indicated that mAb 1D2 was reactive with a series of sialylated proteins with molecular weights of 16–22 kilodaltons. Immunoprecipitates of radiolabelled StMPM protein contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…These data support the preferential effect of ALG.APV-527, activating infiltrating tumor-specific CD8 T cells. The IHC-based 5T4 expression data presented here confirm reported data showing that 5T4 is mainly expressed in tumors with limited expression in normal healthy tissue [11][12][13][14][15]. Tumor antigen dependent drug localization was investigated in a mouse model, demonstrating that ALG.APV-527 can penetrate tumors, and localize to 5T4-expressing tumor cells.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These data support the preferential effect of ALG.APV-527, activating infiltrating tumor-specific CD8 T cells. The IHC-based 5T4 expression data presented here confirm reported data showing that 5T4 is mainly expressed in tumors with limited expression in normal healthy tissue [11][12][13][14][15]. Tumor antigen dependent drug localization was investigated in a mouse model, demonstrating that ALG.APV-527 can penetrate tumors, and localize to 5T4-expressing tumor cells.…”
Section: Discussionsupporting
confidence: 86%
“…5T4 expression was evaluated in both healthy and tumor tissue micro-arrays (TMAs). 5T4 expression in normal healthy tissue was limited and no membrane 5T4 expression was detected in any major organs including the cardiovascular, respiratory, or hepatic systems and in line with previous reports [11][12][13]. Importantly, 5T4 is not expressed in liver (Fig.…”
Section: Algapv-527 Binds Selectively To 4-1bb and 5t4supporting
confidence: 91%
See 2 more Smart Citations
“…14,15 5T4 is a 72 kDa oncofoetal glycoprotein that is expressed in many solid tumors but shows minimal or no expression in normal tissues. 16 We have shown that 5T4 is widely expressed in mesothelioma tissue and on mesothelioma cell lines. 17 Unlike WT-1 and mesothelin, which display subtype-restricted expression, often excluding the more aggressive sarcomatoid variant, 5T4 expression has been shown in all MPM subtypes.…”
Section: Introductionmentioning
confidence: 86%